Aesthetic posts and cores for metal-free restoration of endodontically treated teeth. - Quintas, A. F.; Dinato, J. C.; Bottino, M. A. (My University, 2000)
Utilization of contemporary post and core systems has facilitated the aesthetic restoration of endodontically treated teeth. Light transmission and biocompatibility have been enhanced by the introduction of metal-free post systems. The periodontal and endodontic status, root length, and histological structure of the devitalized teeth must be considered in order to achieve successful restoration following endodontic treatment. This article presents various restorative criteria for the aesthetic placement and buildup of post and core materials, as well as the preservation of maximum coronal and root structure.
Keywords: biomaterial; biomedical and dental materials; carbon; carbon fiber; glass; glass fiber; resin; tooth cement; cementation; ceramics; chemistry; dental care; dental surgery; endodontics; human; light; mechanical stress; pathology; patient care planning; periodontium; tooth crown; tooth prosthesis; tooth pulp disease; tooth root; treatment outcome; Biocompatible Materials; Carbon; Cementation; Ceramics; Composite Resins; Dental Cements; Dental Materials; Dental Prosthesis Design; Esthetics, Dental; Glass; Humans; Light; Patient Care Planning; Periodontium; Post and Core Technique; Root Canal Therapy; Stress, Mechanical; Tooth Crown; Tooth Preparation, Prosthodontic; Tooth Root; Tooth, Nonvital; Treatment Outcome